Interpreting subdivision in a malocclusion Angle’s classification system among orthodontics - Mohammad Yasim, Masrina; Evangelina, Ida Ayu; Sunaryo, Iwa Rahmat (Padjadjaran Journal of Dentistry, 2012)
Introduction: Angle’s method still seems to be the most popular tool for classification of malocclusion. Confusion arises in the community of Orthodontic regarding the classification and interpretation of subdivision malocclusion in Angle’s classification system. The purpose of this study was to survey orthodontists in West Java to determine their consistency in classifying subdivision malocclusion and their viewpoints on the meaning of subdivision. Methods: The type of research was descriptive with survey method by using questionnaire. The study uses total sampling technique with some inclusion criteria. Data obtained were analyzed and presented in table form. Results: Of the 80 respondents, 71.3% is consistent, 22.5% is doubtful and 6.6% is inconsistent in classifying subdivision malocclusion. 37 respondents (46.25%) believe that subdivision refers to the Class II side, 20 respondents (25%) believe it refers to the Class I side 4 respondents (5%) says subdivision refers to neither Class I nor Class II side and 19 respondents (23.75%) says that subdivision referred to both side. Conclusion: Most of orthodontists are consistent in classifying subdivision malocclusion, majority of the responded orthodontists stated that subdivision refers to the abnormal side of the arches and most of the responded orthodontist use Proffit and Common usage as their source of reference.